ANALISIS ISI KENAIKAN HARGA BBM PADA HARIAN KENDARI POS DAN DAMPAKNYA TERHADAP JUMLAH TANGKAPAN NELAYAN DI KELURAHAN SODOHOA KOTA KENDARI - Ima Astuty Wunawarsih (Jurnal Bisnis Perikanan (Journal of Fishery Business), 2016)
The aim of this research were : (1) to know the impact of the news increase BBM price at Kendari Post Daily to the number of catches at Sodohoa Sub District Kendari City, (2) to know Kendari Post daily contents about increases BBM prices. Population of this research are  all fishermen citizen who subscribe and  reading Kendari Post Daily on January until December 2015 month publication are amount 22 people.The sample taked by census method. Data collected derived by community who reading Kendari Post Daily by comparing catch data before and after reporting increases BBM price. Content analysis variable is tabulated and analyzed by descriptive qualitative using categorization consist of  word, theme, content, frequency of the news, column and place of the news. Rwsult of this research showed that the impact of increases BBM price perceived by fishermen were  the number of catches before reporting increases BBM price are the high category. After reporting increases BBM price the number of catches is decrease. The news content about increases BBM price at Kendari Post Daily, word increases BBM price most of the easy to understand category, theme is the most interesting category, the news content very clear, space the news is medium category, frequency of the news is low category and space of news is in the middle categoryKeywords: Content Analysis, Impact, Increases BBM Price, The Number of Fishermen